Estimating the relationship between Public and Private Inputs for K-12 Education: Evidence from Longitudinal Microdata - Vinson, Philip (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2024)
I examine whether private education expenditures and public K-12 funding are substitutes or complements for households whose children attend public school. Using a longitudinal microdata set, the Panel Study of Income Dynamics, I estimate the response of private household expenditures on education in response to changes in public expenditures. This paper implements a fixed-effects model that controls for unobservable household characteristics. I find evidence of complementarity between public and private education spending with an average elasticity of 2.4.